Satisfaction, stress and burnout of nurse managers and care nurses in Primary Health Care* - Garcia, Gracielle Pereira Aires; Marziale, Maria Helena Palucci (Revista da Escola de Enfermagem da USP, 2021)
Objective: To correlate the indicators of job satisfaction, factors of occupational stress and professional exhaustion among nurse managers and care nurses in Primary Health Care. Method: Descriptive, exploratory field study conducted in 45 units of Primary Health Care in Brazil. The following instruments were used for data collection: Sociodemographic Questionnaire, Work Stress Scale, Burnout Characterization Scale and the Job Satisfaction Questionnaire - S20/23. Results: Participation of 122 nurses (47.5% managers; 62.5% care), 32% had considerable stress levels, indicators of emotional exhaustion, dehumanization and disappointment at work in moderate to high levels. The indicator of satisfaction with the physical work environment did not show significance with variables of professional exhaustion, while satisfaction with hierarchical relations and intrinsic job satisfaction are strongly correlated. Conclusion: There is an association between organizational problems and working conditions that hinder nurses' work. Regardless of the position, job satisfaction is inversely proportional to burnout.